SURGERY OF BRAIN STEM CAVERNOUSES MALFORMATION - V. V. Stupak; Sh. Aul; A. G. Bobylev; M. V. Kutsenko; D. A. Dentsel; T. M. Shogunbekov; V. M. Bon; A. M. Gazeev; A. E. Simonovich; S. V. Tsvetovskiy (Сибирский научный медицинский журнал, 2020)
Cavernous malformations (CM), also known as cavernous angiomas or cavernomas, are benign vascular hamartomas having a sinusoidal type of wall structure.CM occurs in the brain stem with a frequency of 9–35 % of cases. They are most often localized in the brain stem, have a higher risk of hemorrhage compared to supratentorial. After the primary hemorrhage, the risks of recurrent hemorrhages are very high. CM located in the brain stem has not always been subjected to surgical treatment. Conservative treatment was recommended for most patients. At the same time, according to the literature data, mortality reached 20 %, and during radiosurgery up to 8.3 % with recurrence of hemorrhage up to 59 %. The aim of the study was to evaluate the results of surgical treatment of patients with cavernomas of the brain stem. Materials and methods. the study included 16 patients who had hemorrhages in different parts of the brain stem. There were 12 males (75 %) and 4 females (25 %). Indications for surgical treatment were: presence of subacute hematoma, recurrent hemorrhage and progressive symptoms of brain stem damage. All patients were operated using modern methods of microsurgery. Neurophysiological monitoring was performed intraoperatively. Statistical processing was carried out with the program Statistica (version 10). Results. There was no operational mortality. At discharge, patients were assessed on the Rankin scale. Good functional outcomes were achieved in 87.8 % of cases (Rankin 1 – 43.8 %, Rankin 2 – 31.5 %, Rankin 3 – 12.5 %). Summary. Symptomatic malformations of the brain stem are subject to surgical removal when they are anatomically accessible. The use of modern methods of neuroimaging, adequate, sparing surgical approaches, microsurgical techniques for removing the cavernous brain stem, allows us to achieve goodfunctional results in the operated patients, in the absence of postoperative mortality.